2023
DOI: 10.3390/buildings13051169
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Research Topics on Construction Safety and Health Using Semi-Supervised Topic Modeling

Abstract: Safety and health have been one of the major issues in the construction industry worldwide for decades, and the relevant research has correspondingly drawn much attention in the academic field. Considering the expanding size and increasing heterogeneity of this research field, this paper proposes the topic modeling approach to cluster latent topics, extract coherent keywords, and discover evolving trends over the past three decades. Focusing on a total of 1984 articles published in 27 different journal sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Keywords are short phrases that represent the core content of the article. Keyword analysis is crucial because scientific publications contain valuable textual information that can represent the primary interests and hotspots of specific fields [51]. This analysis takes into account both Author Keywords (keywords that are manually entered by authors) and Keywords Plus (keywords that are automatically suggested by programs).…”
Section: Researchers Abstract and Document Analysismentioning
confidence: 99%
“…Keywords are short phrases that represent the core content of the article. Keyword analysis is crucial because scientific publications contain valuable textual information that can represent the primary interests and hotspots of specific fields [51]. This analysis takes into account both Author Keywords (keywords that are manually entered by authors) and Keywords Plus (keywords that are automatically suggested by programs).…”
Section: Researchers Abstract and Document Analysismentioning
confidence: 99%
“…For instance, Liu et al employed text mining in risk assessment to construct knowledge graphs from accident reports [21], while Zhang et al used text mining and natural language processing (NLP) to conduct a comprehensive study of construction safety accident investigation reports [9], and the TF-IDF method was used to optimize the weights and extract the main factors that led to the accidents. Zhou et al utilized the LDA model and related explanatory clustering to identify and analyze the significant areas of research in the field of construction safety and health [22]. Zhong et al [23] proposed an intelligent text mining method combining deep learning and LDA modeling to test the effectiveness of the method with the text of accidents occurring at construction sites on the OSHA website.…”
Section: Status Of Text Miningmentioning
confidence: 99%
“…In response to the importance of diverse data sourcing, it is worth mentioning that while our primary dataset originated from official sources, the inclusion of data from broader platforms, such as social media enterprises, could potentially enhance the comprehensiveness of the analysis. Such datasets, although rich in capturing real-time sentiments, can pose challenges related to data validity, consistency, and potential biases [18].…”
Section: Data Collectionmentioning
confidence: 99%